Patient Knowledge of Provider Training Background and Preferences for Treatment of Foot and Ankle Conditions - Alex W. Nielsen MD; Brian C. Law MD; Glenn G. Shi MD; Jonathan C. Kraus MD (Foot & Ankle Orthopaedics, 2019)
Category: Professional, Patient Care Introduction/Purpose: Differences exist in the training backgrounds of medical providers who treat foot and ankle disorders. Considerable overlap and similarities also exist between podiatric and orthopaedic surgeons, though patients may be unaware of the differences. It is not known to what extent professional training influences how patients seek care. The purpose of this study is to understand patients’ knowledge of the differences in professional training background between podiatry and orthopedic surgery and to determine which factors are important to patients when selecting a provider. Methods: Patient survey data was gathered from Froedtert Memorial Lutheran Hospital and the Mayo Clinic. A 27-question survey was administered to new patients who were referred to the foot and ankle service in an orthopedic department at both institutions. Survey questions included data on patient demographics, patient opinion, and knowledge of differences between podiatry, orthopedics, and other foot and ankle providers. Patients were grouped by provider preference. Univariate and multivariate regressions were used to characterize the study population and determine provider preference. Significance was determined through t-tests, Fisher’s Exact test, and chi-square tests. Results: Of the 169 patients who completed the entire survey, 99 chose “orthopedic surgeon” as their provider of preference for any foot or ankle injury. Between the groups, there was no significant difference in age, healthcare affiliation, previous podiatric visits, level of education, and perceived knowledge about the differences between the two specialties (Table 1). For patients who listed podiatry as their preference, they were less likely to expect their doctor to have completed residency (76.2% vs. 90.7-94.9%, p=0.03). Patients preferred an orthopedic surgeon over a podiatrist for ankle (63.3% vs. 9.5%, p<0.001) and knee injuries (82.8% vs. 5.8%, p<0.001), while they preferred a podiatrist for toe pain (42.6% vs. 27.8%, p<0.001). 76.3% of patients thought orthopaedic surgeons and podiatrist undergo the same professional training. Conclusion: Foot and ankle patients have poor understanding of the different medical and surgical training backgrounds between a podiatrist and orthopedic surgeon. The majority of patients believe podiatrist and orthopaedic surgeons have the same professional training. However, patients also believed orthopaedic surgeons have a longer training period, though it was still underestimated by three years. Patients preferred care for podiatrist with conditions affecting the toes and orthopaedic surgeons for all other conditions.